Assessing the degree of perceived risk in adoption of mobile payment system by retailers in India. (21st March 2022) - Ramtiyal, Bharti; Verma, Deepak; Rathore, Ajay Pal Singh
Mobile payment system (MPS) is an integral component of service delivery system in almost every service organisation and in order to achieve operational excellence (OpEx) in services, one needs a tool to assess the underlying perceived risk with a given retailer segment. MPS is important in terms of economics, security and the productivity of a business. This study assesses the degree of PR in adoption of MPS by various types of retailers in Indian context. The study first prioritises various factors of PR from a retailer's point of view using fuzzy analytic hierarchy process (FAHP). Further, using the output of FAHP the degree of PR in adoption of MPS is established for three formats of retailing. Additionally, it supports small retailer's base by creating more awareness among government bodies and managers as to how to reduce the PR associated with MPS and take a step towards achieving OpEx in service delivery system.